ANALISIS PENDAPATAN DAN FAKTOR PENENTU PRODUKSI KAKAO HASIL SAMBUNG SAMPING DI KABUPATEN KONAWE - Rusdin Rusdin; Zainal Abidin (Mega Aktiva, 2018)
Extensive cocoa plantations in Southeast Sulawesi at 2013 were approximately 245 624 ha, which consists of 177 996 ha of productive plants, 38.970 ha and 28.658 ha unproductive unproductive plants. Cocoa productivity in Southeast Sulawesi as a whole is 0.754 t/ha. The low productivity of cocoa was due to several factors, namely: the use of random seed, still high PBK pest attack, low levels of cultivation technology, as well as the age old cocoa plants. The study was conducted in March - June 2014 Andomesinggu village, district. Besulutu, Konawe. The study results showed that the average productivity of the cocoa plant side grafting 2-3 years amounted to 380 kg/ha, profit of Rp. 7.160.900, -. with the value of RC ratio  of 4.22, meaning farming in the district Konawe economically feasible to be developed. Variables land area is very significant in improving cocoa production and is positive. Similarly, production factors KCl fertilizer, organic fertilizer real berpengatuh to increase cocoa production. While the factors of production of NPK fertilizer, Urea, ZA and pesticides did not significantly decline in production (negative values).